A Possible Type IV Hypersensitivity Reaction to Older Antiepileptic Drugs During and After Recovery from COVID-19 Infection - Khosravi, Mohsen (Pharmacopsychiatry, 2021)
Nearly two years after the onset of the coronavirus disease 2019 (COVID-19) pandemic, healthcare workers face new and unexpected complications. Although accelerating the vaccination process in recent months has reduced the incidence and mortality of the COVID-19 infection, the general population (particularly vulnerable groups) remains at risk of new severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants. Over the last two months, Iran has encountered the fifth wave of the COVID-19 pandemic, i. e., the B.1.617.2 (Delta) variant of the SARS-CoV-2, with faster infectiousness and higher severity and mortality among hospitalized patients 1. Although fever, cough, and expectoration are the most common clinical features of COVID-19, recent studies have indicated an increasing number of skin manifestation reports in the disease. Besides, there is growing evidence that underlying SARS-CoV-2 infection may increase the risk of adverse drug reactions 2. However, the enduring concern in our medical centers in recent days is a raised incidence of Stevens-Johnson syndrome (SJS) in recovered COVID-19 patients following monotherapy with older antiepileptic drugs (0.004 vs. 0.0008% – i. e., 5 times higher than the pre-COVID-19 period) 3. It is worth noting that these patients did not have any history of SJS/toxic epidermal necrolysis (TEN) or additional etiopathogenic factors, including infections, genetic factors (particularly HLA-B*1502 allele), and malignancy. Furthermore, for many years before developing the COVID-19 and recovering from it, they had been treated with the above drugs without showing any cutaneous hypersensitivity reactions. These observational findings raise two important questions: (i) Could a history of the COVID-19 infection be a potential risk factor for type IV hypersensitivity reactions to older antiepileptic drugs? (ii) If so, what are its mechanisms of action?